PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID UNTUK PEMBELAJARAN FISIKA DI SEKOLAH MENENGAH ATAS - Wulandari, Nyemas; Aunurrahman, Aunurrahman; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Purpose of this research are : 1) Android based interactive Learning Media design For Learning Physisc In Senior High School; 2) Android based interactive Learning Media Profiles For Learning Physisc In Senior High School; 3) The Implementation Of Learning Using interactive Learning Media For Learning Physisc In Senior High School; 4) Student Learning outcomes after using interactive learning media basedÂ on android for Learning Physisc In Senior High School. In this research and development using Four D Development design models. This research was conducted in SMA Negeri 1 Ngabang. Product development trials are carried out throughÂ expert validation stages, one to one trials, medium groups and large groups. Data collection techniques used are direct observation techniques, indirect communication techniques, measurement techniques, and documentaries with observation sheet collecting tools, student response questionnaires, test questions and documentation. The analysis of the data used for the results of validation and obeservations is to divide the total score obtained by the maximum score. Cognitive learning acquisition of 77,24 is included in good category., affective domain is 85,65% included in the excellent category and psychomotor domain of 79,17 % included in good category.Â Keywords : Android, Learning Media, Learning Outcomes